World Market and Agrarian Transformation: The Case of Neo-Liberal Chile - Gomez, Sergio; Goldfrank, W.L. (The International Journal of Sociology of Agriculture and Food, 1991)
The recent Chilean agrarian transformation is analyzed, with special focus on the export boom in fresh fruit. The expansion and diversification of the sector are explored, and its structural characteristics explicated as "semi-peripheral." Changing consumption patterns in the advanced countries and technological improvements in storage and transport are credited with facilitating growth. Increases in national basic foodstuff production are explained as a departure from neo-liberal practice. The heterogeneous composition of both the owning and the producing classes is outlined. Resumen Mercado Mundial y Transformación Agraria: El Caso del Neoliberalismo en Chile La reciente transformación agraria chilena es analizada haciendo especial énfasis en el boom de las exportaciones de frutas frescas. Se explora la expansión y diversificación de este sector y su caractersítica estructural es explicada como "semiperiférica". El cambio en los patrones de consumo de los países avanzados y el perfeccionamiento tecnológico en el transporte y almacenamiento son facilidades que posibilitan su crecimiento. El incremento de la producción básica alimentaria nacianal es explicado como consecuencia de la apertura hacia prácticas neoliberales. Como consecuencia de ello, la composición heterogénea tanto de las clases productoras como poseedoras se está terminado.